Genomic analyses of Burkholderia respiratory isolates indicates two evolutionarily distinct B. anthina clades - Pham, Amy; Volmer, James G.; Chambers, Daniel C.; Smith, Daniel J.; Reid, David W.; Burr, Lucy; Wells, Timothy J. (Frontiers in Microbiology, 2023)
The Burkholderia cepacia complex (BCC) encompasses a group of at least 22 genetically distinct gram-negatives bacterial species ubiquitous in nature. Recognised as a group of genetically and phenotypically flexible species, the BCC inhabits diverse ecological niches causing both plant and human diseases. Comparative genomic analysis provides an in depth understanding into the population biology, phylogenetic relationship, and genomic architecture of species. Here, we genomically characterise Burkholderia anthina isolated from patients with chronic lung infections, an understudied pathogen within the Burkholderia cepacia complex, and demonstrate that B. anthina is polyphyletic and constitutes two distinct evolutionary lineages. Core- and pan-genome analyses demonstrated substantial metabolic diversity, with B. anthina Clade I enriched in genes associated with microbial metabolism in diverse environments, including degradation of aromatic compounds and metabolism of xenobiotics, while B. anthina Clade II demonstrated an enhanced capability for siderophore biosynthesis. Based on our phylogenetic and comparative genomic analyses, we suggest stratifying B anthina to recognise a distinct species harbouring increased potential for iron metabolism via siderophore synthesis, for which we propose the name Burkholderia anthinoferum (sp. nov.).